2015
DOI: 10.4317/jced.52568
|View full text |Cite
|
Sign up to set email alerts
|

The effects of silver nanoparticles on antimicrobial activity of ProRoot mineral trioxide aggregate (MTA) and calcium enriched mixture (CEM)

Abstract: BackgroundAlthough, mineral trioxide aggregate (MTA) and new experimental cement (CEM) are good root filling cements, but had no or low antimicrobial activities. The aim of this study was to evaluate the effects of addition of silver nanoparticles (SNP) to these two cements on antimicrobial effects against five most dental infection related microorganisms.Material and MethodsTwo suspensions of 100 and 200 ppm of SNP were prepared and 180 μl of microbial suspension with 1.5 × 108 CFU/ml of each respected microo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 26 publications
2
16
0
1
Order By: Relevance
“…In endodontic treatments, application of different concentrations of SNPs in combination with MTA and CEM had shown an antibacterial effect against Escherichia coli, Enterococcus faecalis, Candida albicans, and Actinomyces spp. [ 24 ]. The membrane designed in the present study succeeded to offer suitable antimicrobial properties like the previously mentioned studies.…”
Section: Discussionmentioning
confidence: 99%
“…In endodontic treatments, application of different concentrations of SNPs in combination with MTA and CEM had shown an antibacterial effect against Escherichia coli, Enterococcus faecalis, Candida albicans, and Actinomyces spp. [ 24 ]. The membrane designed in the present study succeeded to offer suitable antimicrobial properties like the previously mentioned studies.…”
Section: Discussionmentioning
confidence: 99%
“…Some researchers have introduced nanosilver-gutta-percha, as an attempt to improve the antibacterial effect of gutta-percha ( 36 ). Other studies demonstrated the bactericidal activity of composite resins containing silver nanoparticles and the positive effects of AgNPs on MTA antimicrobial activities ( 32 , 37 ).…”
Section: Discussionmentioning
confidence: 93%
“…The addition of NPs promoted antibacterial activity in Ca(OH) 2 [72,73] and other filling materials [74,75,76,77]. Calcium silicate cement such as mineral trioxide aggregate (MTA) and Portland cement (PC) showed antimicrobial effects, and their antimicrobial activity was significantly enhanced by mixing them with different concentrations of AgNPs [75,78]. Similarly, the addition of QPEI NPs also reduced bacteria viability and promoted cell death [48,76,79].…”
Section: Antimicrobial Applications In Dentistrymentioning
confidence: 99%